A preliminary study of the gas hydrate stability zone in a gas hydrate potential region of China. Issue 4 (10th December 2019) - Xiao, Kun; Zou, Changchun; Yang, Yaxin; Zhang, Hua; Li, Hongxing; Qin, Zhen
Abstract: Due to its significance for gas hydrate accumulation, the gas hydrate stability zone (GHSZ) is an essential condition for successful gas hydrate exploration and is usually controlled by three main factors: gas components, geothermal gradient, and permafrost thickness. Based on the core and conventional log data of gas hydrate potential region, the CSMHYD program was adopted to simulate the influences of above three factors on the thickness of the GHSZ. When the gas components of the gas hydrate were CH4, C2 H6, and C3 H8, with the CH4 percentage ranging from 50% to 100%, the average GHSZ thickness can reach 1000 m according to the forward simulation results. When the gas hydrate was composed of CH4 and one of C2 H6, C3 H8, H2 S, and CO2, the influence order of the above four gases on the thickness of GHSZ is as follows: H2 S ＞ C2 H6 ＞ C3 H8 ＞ CO2 . Under the gas components of 90% CH4, 5% C2 H6, and 5% C3 H8, the thickness of GHSZ decreased rapidly as the geothermal gradient increased following an exponential relation with a correlation of 99.92% and increased slowly as permafrost thickness increased following a linear relation with a correlation of 99.9%. In addition, the thickness of a gas hydrate favorable reservoir was determined by comprehensive log methods as 500 m. We conclude that a reservoir within 500 m below the permafrost layer is favorable for gas hydrate reservoir formation. Abstract : The CSMHYD program is adopted to simulate the influences of three main factors on the GHSZ thickness. The response of influence factors changes on the GHSZ thickness is obvious. Identifying the thickness of gas hydrate favorable reservoir by comprehensive log methods.